Accelerating Construction Industry Development - Kumaraswamy, Mohan M. (Penerbit Universiti Sains Malaysia, 2006)
The needs for construction industry development are initially viewed from the broader perspectives of imperatives for infrastructure development and national development. All these are clearly more critical in developing countries. A non-exhaustive set of potential drivers and common barriers to construction industry development is identified from previous research. These suggest the usefulness of consolidating a cluster of recent proposals and exercises aiming at (a) construction organisation development in terms of an over-arching management support system model, as well as improved information and knowledge management; and (b) project team development in the context of relationally integrated teams and supply chains, joint risk management and ‘technology and knowledge exchange’ in joint ventures, as well as longer term public private partnerships. These apparently disparate research thrusts are threaded together into a pattern that may inspire, if not feed, specific research and development (R&D) agendas for construction industry development in different countries according to their own priorities, constraints and stages of infrastructure and national development.